Managing the Supply Chain for Global Success a Case Study of Indian Auto Component Industry - Jagannathan, Lakshmi; Jacob, Fatima (Ushus Journal of Business Management, 2007)
From a country that sold just a few hundred thousand cars annually a decade ago, over a million cars roll out of Indian factories every year to fuel a vibrant component industry with global quality and technology standards. McKinsey and Company has predicted that the Indian automobile component industry would grow to a whopping $33-40 billion by 2015, out of which the global outsourcing of components could be to the tune of $20-25 billion! The Indian auto component manufacturers would see an exponential growth in output over the next decade. The industry is growing at a compounded rate of 20-25%, much faster than that of the domestic market (10-14 %). Many consider this growth in exports as just the tip of the iceberg similar to that witnessed by the information technology industry in the early 1990s. The sustained growth of Indian auto component industry can be attributed to many factors, but primarily to efficient management of the supply chain.